2016
DOI: 10.1007/s00775-016-1371-x
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectroscopic study of the interaction between Co(II)rrinoids and the ATP:corrinoid adenosyltransferase PduO from Lactobacillus reuteri

Abstract: The human-type ATP:corrinoid adenosyltransferase PduO from Lactobacillus reuteri (LrPduO) catalyzes the adenosylation of Co(II)rrinoids to generate adenosylcobalamin (AdoCbl) or adenosylcobinamide (AdoCbi+). This process requires the formation of “supernucleophilic” Co(I)rrinoid intermediates in the enzyme active site that are properly positioned to abstract the adeonsyl moiety from co-substrate ATP. Previous magnetic circular dichroism (MCD) spectroscopic and X-ray crystallographic analyses revealed that LrPd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…Lactobacillus can play a role by producing lactic acid and extracting energy from the fermentation of different sugars, which helps regulate the corpulence metabolism in people with obesity (50). Because bariatric surgery delays glucose and amino absorption in the host tract, the increase in simple sugars and amino acids in the large intestine may activate the colonic bacteria to derive energy from malabsorbed nutrients (51,52,53). Although C. comes has been found to be correlated with the inflammation procedure and bile acid homeostasis, the mechanism that affects the host metabolism remains unclear, which suggests more investigations (54,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus can play a role by producing lactic acid and extracting energy from the fermentation of different sugars, which helps regulate the corpulence metabolism in people with obesity (50). Because bariatric surgery delays glucose and amino absorption in the host tract, the increase in simple sugars and amino acids in the large intestine may activate the colonic bacteria to derive energy from malabsorbed nutrients (51,52,53). Although C. comes has been found to be correlated with the inflammation procedure and bile acid homeostasis, the mechanism that affects the host metabolism remains unclear, which suggests more investigations (54,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…7,13 rR spectroscopy has been employed, for example, to assess the extent of corrin ring perturbations imposed on Co II cobalamin (Co II Cbl) by the adenosyltransferase PduO. 14 The binding of Co II Cbl to PduO in the presence of co-substrate ATP was found to affect both the frequencies and relative intensities of corrin stretching modes. Through a combination of spectroscopic and computational methods, it was demonstrated that these changes arise from the tight binding imposed by PduO to prevent repositioning of its Co II Cbl substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous computational analyses of the vibrational spectra of cobalamins have either neglected resonance enhancement of vibrational modes 39−42 or considered the relative resonance enhancement of only a select number of corrin stretching modes. 12,14 In this paper, we present a detailed analysis of rR spectra and vibronic coupling in CNCbl as predicted by the B3LYP and BP86 functionals. We used these data to guide further rR spectroscopic studies and identified, for the first time, isotope-sensitive features that can be attributed to the Co−C stretching and Co−C−N bending modes of CNCbl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, vitamin B 12 and its derivatives have been extensively investigated by means of various methods including electronic absorption (UV-Vis) [ 23 , 24 , 25 , 26 ] as well as Raman spectroscopy techniques [ 27 , 28 , 29 , 30 , 31 , 32 ]. These methods supported by a theoretical approach guarantee insight into the complex nature and electronic or vibrational properties of corrinoids.…”
Section: Introductionmentioning
confidence: 99%